Technology-based measurements for screening, monitoring and preventing frailty - Elgert, Lena; Schwenk, Michael; Bauer, Jürgen M. (Zeitschrift für Gerontologie und Geriatrie, 2016)
BACKGROUND AND OBJECTIVE: Sensor technology, in particular wearable inertial sensors, has the potential to help researchers objectively assess the functionality of older adults. The following review provides an overview about the possible use of sensor technology to detect and prevent pre-frailty and frailty. METHOD: A systematic literature search in PubMed and the Cochrane Library was conducted. Articles were selected according to the following criteria: frail and/or pre-frail population, use of wearable and non-wearable sensor technology to measure or enhance human movements or activities of daily living and a focus on frailty assessment.